Economic Conflict Management and Crisis Resolution: A Review from Islamic Economic Law Perspective - Saltanat Tashbolotova; Murshed Sami Mohammad Mahmood; Nadema Aljaf; Farah Mohammed Abdulrahman; Shia Radha Tahir; Hossam Najm Abboud Al-Bayat; Saad Qasim Abbas; Salah Ajmi Jami; Ahmed Abduladheem Abdullah (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article explores the intersection between economic conflict management and the contributions of Islamic economists to post-conflict stability and crisis resolution. This study uses quantitative economic models combined with Islamic finance principles to examine how rational economic planning and ethical frameworks can help alleviate economic challenges. The analysis employs linear programming, econometric minimization, and optimal dynamic programming to simulate resource allocation, price level control, and cost estimation. At the same time, this study highlights the importance of economic Intelligence and coordination in anticipating and responding to the challenges of the modern world. This study also examines how Islamic economic instruments, such as zakât, infâq, and waqf, can impact post-conflict economic recovery in specific countries. Evidence suggests that efficient zakât collection and the utilization of waqf in social programs are positively associated with GDP recovery, employment stabilization, and social welfare.